Investigating the challenges working-class women face in the construction industry-RSA - Ngqentsu, Mangesi Benson (Department of Sociology, 2023)
South Africa's construction industry remains a male-dominated economic sector. Despite numerous progressive and transformative efforts, male domination and patriarchal behaviour continue to pose daunting challenges to women. This study investigates working-class women's challenges in the construction industry and considers possible avenues to ensure substantive transformation. The study provides critical insights into stubborn and widespread patriarchy within the industry by drawing on a range of feminist and Marxist theoretical perspectives. The study uses qualitative research techniques, (i) three focus group discussions, (ii) six in-depth interviews and (iii) secondary data to demonstrate the prevalence of significant oppressive patriarchal and exploitative relations that marginalise women. This study shows that women in the construction industry experience multitudes of challenges, not only from men as an expression of patriarchy but also as an entrenched ideology supporting structural and systemic features of capitalist exploitation and oppression within the industry itself. Women are peripheralized, relegated to low-wage junior roles and subjected to dehumanising treatment, including widespread sexual harassment. Thus, this study's results essentially show that working-class women constitute the bulk of unskilled labour, semi-skilled and junior positions in the industry. It is, therefore, incumbent on scholars and policymakers to motivate deeper analysis to generate behavioural and systemic changes to achieve substantive inclusion and empowerment of women in the sector. Notably, the study recommends that employers and the construction industry's trade union movement (i) establish a single, central bargaining council merging civil engineering, manufacturing and building, (ii) establish effective Health and Safety and Employment Equity and Transformation Committees to drive and monitor issues related to skilling of workers, (iii) provide education on health and safety matters. Evidence and analysis provide fresh insights, including (i) a privileged section of white women positioned as senior administrative assistants whilst their black counter-parts occupy unskilled and semi-skilled positions, (ii) ix the context within which women earn lower wages than men, and (iii) how femininity is conveniently used as an excuse to keep women in peripheral and junior positions.